CAN THE ANTEROLATERAL THIGH FLAP REPLACE THE RECTUS ABDOMINIS FREE FLAP IN THE RECONSTRUCTION OF COMPLEX MAXILLARY DEFECTS? - Eitezaz, Farhan Ahmed; Rashid, Mamoon; Yousaf, Shumaila; Rehman, Ishtiaq Ur; Fatima, Samia; Masud, Mehreen; Sanober, Aamna; Khan, Adeela Hussain; Rashid, Haroon Ur (Journal of Ayub Medical College Abbottabad, 2018)
Abstract : Background/Objective : The aim of this study is to compare the Anterolateral Thigh Flap(ALTF) to the standard option like the Rectus Abdominis Free Flap(RAMFF) for the reconstruction of complex maxillary defects.’¨ Materials and Methods: This study was conducted at the Department of Plastic and Reconstructive Surgery, Shifa International Hospital Islamabad, Pakistan. In the past 08 years between 2009 to 2016 patients of all age groups with complex maxillectomy defects, (Type III and IV according to Cordeiro classification) resulting from tumour resection, trauma, osteoradionecrosis or infection, underwent reconstruction with the free anterolateral thigh flap and the rectus abdominis free flap. All the patients with tumours were discussed in the head & neck multidisciplinary team meeting. Results: Over a period of 8 years, 49 Rectus Abdominis free flaps and 32 Anterolateral thigh free flaps were performed for reconstruction of Type III and IV maxillectomy defects. The predominant cause of the defects was tumour excision followed by defects resulting from mucormycosis. The patients’ ages ranged from 6 to 80 years. The follow up was weekly for 1 month and then 3 monthly for the 1st year, 6 monthly for 2nd year and then yearly. All the patients had an uneventful immediate recovery. There were increase incidence of donor site morbidity in the RAMFF group as compared to the ALTF group. There was 1 flap loss in the RAMFF group series. Conclusions : Our experience suggests that the ALTF has advantages over the RAMFF in terms of the donor site morbidity, operative time and postoperative recovery in the reconstruction of complex maxillectomy defects. Keywords: Microvascular maxillary reconstruction, Cordeiro Type III Maxillary defect, Cordeiro Type IV Maxillary defect, Free flaps Complications. Anterolateral Thigh free flap, Rectus Abdominis free flap. Background: Maxilla is perhaps the most essential and visible part of the mid-face. It is a three-dimensional structure and when reconstructing maxillectomy defects the principles of aesthetics as well as the best functional outcomes are taken into account. The aim of this study is to compare the Anterolateral Thigh Flap (ALTF) to the standard option like the Rectus Abdominis Free Flap (RAMFF) for the reconstruction of complex maxillary defects. Methods: This descriptive case series was conducted at the Department of Plastic and Reconstructive Surgery, Shifa International Hospital Islamabad, Pakistan from 2009 to 2016. Patients of all age groups with complex maxillectomy defects, (Type III and IV according to Cordeiro classification) resulting from tumour resection, trauma, osteoradionecrosis or infection, underwent reconstruction with the free anterolateral thigh flap and the rectus abdominis free flap. Results: Over a period of 8 years, 49 Rectus Abdominis free flaps and 32 Anterolateral thigh free flaps were performed for reconstruction of Type III and IV maxillectomy defects. The follow up was weekly for 1 month and then 3 monthly for the 1st year, 6 monthly for 2nd year and then yearly. All the patients had an uneventful immediate recovery. Conclusion: ALTF has advantages over the RAMFF in terms of the donor site morbidity, operative time and postoperative recovery in the reconstruction of complex maxillectomy defects. Keywords: Microvascular maxillary reconstruction; Cordeiro Type III Maxillary defect; Cordeiro Type IV Maxillary defect; Free flaps Complications; Anterolateral Thigh free flap; Rectus Abdominis free flap.